Glass Fibre Reinforced Concrete: Design & Analysis - Kumar, Tarun (IJRDO - Journal of Mechanical And Civil Engineering, 2016)
Fiber-reinforced concrete (FRC) is concrete containing fibrous material which increases its structural integrity. It contains short discrete fibers that are uniformly distributed and randomly oriented. Glass fiber reinforced concrete, also known as GFRC or GRC, is a type of fiber reinforced concrete. Glass fiber concretes are mainly used in exterior building façade panels and as architectural precast concrete.This paper describe the use of fibres which are of different shapes and sizes in different forms as all know the function of the fibre based concrete is to arrest cracks, fibre composites possess increased extensibility and tensile strength, both at first crack and at ultimate, particular under flexural loading; and the fibres are able to hold the matrix together even after extensive cracking.so the purpose of the paper is to show the various forms of fibres used in concrete and discuss about their properties and applications.